(untitled) (Research, Society and Development, 2022)
Context: Polycystic Ovarian Syndrome (PCOS) is a common multisystem disease that causes reproductive, metabolic and psychological changes. Lately, the use of medicinal plants has grown considerably in the hope of reducing the side effects of synthetic drugs and in an attempt to reduce harm and costs. Objective: Analyze the use of medicinal plants that are used in PCOS from an integrative literature review, in order to verify the pharmacological effects caused by their use in PCOS. Methodology: An integrative literature review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines through searches in PubMed, Scielo and Scopus databases to select ethnobotanical, ethnopharmacological, preclinical and clinical studies, published in full in the last 10 years (2012 – 2022), in English, Portuguese and Spanish using health descriptors. Results: The ten publications analyzed showed ten families and 11 plant species, which, in general, showed antiandrogenic activities. Conclusions: With the exception of Foeniculum vulgare, all other medicinal plants analyzed in this study have anti-androgenic effects on PCOS. However, these species need better clinical and toxicological evaluations regarding their use in order to provide a safe and effective therapy.